Comparison and Evaluation of Alveolar Bone Around Lower Central Incisors in Class III and Class I Patients - Tülin Taner; Ezgi Atik; Hande Gorucu-coskuner (Cumhuriyet University, 2018)
Objectives: The aim was to compare the alveolar bone support of mandibular central incisors in subjects with Class III and Class I skeletal patterns using cone-beam computed tomography (CBCT). Materials and Methods: Group 1 included 20 patients (mean age=19.78±2.80) with Class III malocclusion (mean ANB°=-2.77±3.69), mesofacial growth pattern (FMA°=27.03 ±5.11) and lingual-inclined mandibular incisors (IMPA°<85). Group 2 included 20 patients (mean age=20.85±3.97) with Class I malocclusion (mean ANB°=2.94 ±1.46), mesofacial growth pattern (FMA°=25.67±6.83) and normal inclined mandibular incisors (85<IMPA°<95). Vertical alveolar bone level and alveolar bone thickness (ABT) of total 80 mandibular central incisors (40 from each group) were evaluated. Buccal, lingual and total ABT were measured at the crestal, midroot, and apical levels. Buccal (BACH) and lingual (LACH) alveolar crestal heights were also evaluated.  Mann-Whitney U, independent samples-t-tests, and Spearman's rank correlation analysis were applied for statistical analysis. Results: The lingual ABT at the crestal and midroot level, buccal ABT at the apical level, and total ABT at all levels were significantly lower in Group 1 than Group 2 (p<0.05). There was a negative correlation between the buccal (r=-0.324; p=0.042) ABT at the apical level and mandibular plane angle. The change in mandibular incisor inclination was positively correlated with buccal ABT at the apical level (r=0.463; p=0.003) and lingual ABT at the crestal level (r=0.550;p<0.001). BACH was significantly higher in Group 1 (2.21±1.48 mm) compared to Group 2 (1.42±0.17 mm) (p < 0.05). Conclusions: In subjects with Class III deformities, mandibular central incisors have less bone support especially at the buccal side of the alveolar bone at the apical level and lingual side of the alveolar bone at the crestal and midroot levels. Rate of change in mandibular incisor inclination and mandibular plane angle can be thought as significant factors that may influence alveolar bone thickness.